Application Of Cooperative Learning Type (TGT) Team Games Tournament Learning Model Toward Passing Down Volyball For Class Viii Students At SMP N 2 Pangean: Penerapan Model Pembelajaran Cooperative Learning Tipe (TGT) Team Games Tournament Terhadap Passing Bawah Bola Voli Siswa Kelas Viii Di SMP N 2 Pangean - Pindri Despika; Daharis Daharis (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Learning to pass under volleyball will not succeed without a well-thought-out plan in the learning process. Learning methods were developed from the differences in the characteristics of students who varied. Therefore, we need an appropriate learning method according to the characteristics of each student. The method that is often used in learning to pass under volleyball is the direct method or the Team Games Tournament (TGT) method. In learning model cooperative type Team Games Tournament (TGT) activity mostly educators using this to give motivation students, increase students interest, and make the atmosphere of learning be enjoyable. This type of research is Classroom Action Research (CAR). The research subjects in this classroom action research were 20 class VIII students, consisting of 8 male students and 12 female students. Data collection using test and measurement and observation methods.